If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 9) = 12 + -3(y + 14) + 3y Reorder the terms: 2(9 + y) = 12 + -3(y + 14) + 3y (9 * 2 + y * 2) = 12 + -3(y + 14) + 3y (18 + 2y) = 12 + -3(y + 14) + 3y Reorder the terms: 18 + 2y = 12 + -3(14 + y) + 3y 18 + 2y = 12 + (14 * -3 + y * -3) + 3y 18 + 2y = 12 + (-42 + -3y) + 3y Combine like terms: 12 + -42 = -30 18 + 2y = -30 + -3y + 3y Combine like terms: -3y + 3y = 0 18 + 2y = -30 + 0 18 + 2y = -30 Solving 18 + 2y = -30 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2y = -30 + -18 Combine like terms: 18 + -18 = 0 0 + 2y = -30 + -18 2y = -30 + -18 Combine like terms: -30 + -18 = -48 2y = -48 Divide each side by '2'. y = -24 Simplifying y = -24
| 4x-23=3x+16 | | 6=2(1+w) | | 500=4x^2-40x+400 | | 2(x-12)=27 | | 9(m-3)=5m+9 | | 5(2a+7)=2(3a+4) | | 815/12=a | | 16+3x=19+21x | | -27.083x-16.819=-11.246 | | x+91=x+97 | | 11e=9e+4 | | 5+2x=9.50 | | 4d^2+64=0 | | 2x-3x=14 | | -3n+11-7n=-13 | | 2z-1=z+8-22 | | x+91=x+971 | | x^2-22xy-48y^2= | | x/4-10=-13 | | -3+11-7n=-13 | | 6c-12+4c=8c | | -3+9=a | | 81-(6*9)=1 | | 19f^2-17k-2=0 | | 3s-4+6s+7= | | 18x^2+9x-20=0 | | d^2-14d+13=0 | | -6/5=a | | 16x-5=105 | | -5(4r+8)=16-3r | | (7x+2)(3x^3-14x-5)=0 | | 7x=434 |